Emancipation life paths of Portuguese Cigano/Roma women - Magano, O. (2022)
In Portuguese society, some Cigano/Roma women, during their life paths, distance themselves from the Cigano cultural tradition, particularly in regard to marriage, schooling, employment and social life. On the one hand, there is a feeling of attachment to traditional values as family pressure to marry or in relation to gender differentiation; on the other hand, these women express a desire for empowerment autonomy and emancipation in order to draw up their own trajectories and life projects. The results obtained with 21 in-depth interviews, 10 women and 11 men, indicate that Cigano women face greater difficulties with regard to early and inbred marriage and are more prone to be victims of family and domestic violence, but they are also the main drivers of change and social transformation of Cigano/Roma families.